Taking liberties : gender, transgressive patriotism, and Polish drama, 1786-1989 - Filipowicz, Halina (Ohio University Press Polish and Polish-American studies series., 2014)
"As narrow, nationalist views of patriotic allegiance have become widespread and are routinely invoked to justify everything from flag-waving triumphalism to xenophobic bigotry, the concept of a nonnationalist patriotism has vanished from public conversation. Taking Liberties is a thoughtful and deliberative study of what may be called patriotism without borders: a nonnational form of loyalty compatible with the universal principles and practices of democracy and human rights, respectful of ethnic and cultural diversity, and, overall, open-minded and inclusive. Moving beyond a traditional study of Polish dramatic literature, Halina Filipowicz turns to the plays themselves and to archival materials, ranging from parliamentary speeches to polemical pamphlets and verse broadsides, to explore the cultural phenomenon of transgressive patriotism and its implications for society in the twenty-first century. Three major themes unite this exploration: controversies over "true" and "false" patriotism; disputes over class and gender boundaries; and imaginative attempts to expand the meaning of "us" to take in "not-us," and perhaps even to undo the whole opposition between "us" and "them." In addition to recovering lost or forgotten materials, the author builds an innovative conceptual and methodological framework to make sense of those materials and to challenge many long-standing assumptions about Polish cultural and intellectual history. Taking Liberties contributes to the debate over the meaning and practice of patriotism"--